2013
DOI: 10.3126/mjsbh.v11i1.7767
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Skin Changes During Pregnancy.

Abstract: Introducti on: Approximately 90% pregnant women are associated with skin changes. The skin undergoes profound alterati ons during pregnancy as a result of endocrine, metabolic and immunologic changes. Some of these are trivial and chiefl y cosmeti c, producing no or minor symptoms, others can be distressing and/or of major medical importance. For the necessity of proper and complex care of the pregnant woman,the knowledge about the changes are crucial. The ability of precise diagnosis of physiological skin cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Abdomen & buttocks are most commonly affected areas. This is consistent with findings of other studies by Shanta Ikram 16 & Shah et al 17 Vascular changes were also found in our study. Gingival hyperemia was present in 40% of patients.…”
Section: Discussionsupporting
confidence: 94%
“…Abdomen & buttocks are most commonly affected areas. This is consistent with findings of other studies by Shanta Ikram 16 & Shah et al 17 Vascular changes were also found in our study. Gingival hyperemia was present in 40% of patients.…”
Section: Discussionsupporting
confidence: 94%